RAPID URINE SCREENING FOR BACTERIURIA IN CHILDREN USING MICROBIOLOGY ANALYZER, COMBINING PHOTOMETRIC AND COHERENT FLUCTUATION NEPHELOMETRIC METHODS - A. S. Gur’ev (Sankt-Peterburg : NIIÈM imeni Pastera, 2017)
One of the most widespread microbiological analyses in clinical practice is urine culture, and up to 80% of urine samples turn out to be negative. In this study we demonstrate applicability of coherent fluctuating nephelometry (CFN) method for rapid urine screening and negative samples identification for the purpose of reducing the workload of microbiological laboratory. 205 urine samples were tested by conventional culture method (CCM) and using CFN-analyzer. The agreement between CCM and CFN was 87.8%. Compared to CCM, CFN demonstrated sensitivity — 94.5%, specificity — 85.3%, negative predictive value — 97.7%, positive predictive value — 70.3%. In this study CFN-analyzer allowed to identify 85.3% of negative urine samples (63.9% of all tested samples) within 4 hours, and 94.5% of positive samples were retained for later CCM. Moreover none of samples with count ≥ 104 CFU/ml was omitted.